Primary Hepatic Lymphoma in a Patient with Rheumatoid Arthritis Treated with Methotrexate - Tatsumi, Goichi; Ukyo, Naoya; Hirata, Hirokazu; Tsudo, Mitsuru (Case Reports in Hematology, 2014)
Primary hepatic lymphoma (PHL) has rarely been reported in patients with immunosuppression. We herein describe a case of Epstein-Barr virus- (EBV-) positive PHL in a 67-year-old Japanese woman receiving methotrexate (MTX) treatment for rheumatoid arthritis (RA). The patient, who had been receiving MTX therapy for more than 6 years, presented with low-grade fever and abdominal pain. Initial laboratory tests showed mildly elevated liver enzymes with normal levels of alpha-fetoprotein and carcinoembryonic antigen, and computed tomography scans revealed multiple hepatic tumors with no lymph-node swelling. Examination of liver specimens obtained via ultrasonography-guided needle biopsy indicated EBV-positive diffuse large B cell lymphoma; therefore, she was diagnosed with PHL. MTX was discontinued, and she was carefully monitored thereafter owing to the prolonged history of MTX administration for RA. Rapid progression of PHL was observed; therefore 10 days after the PHL diagnosis, she received 6 cycles of R-THP-COP (rituximab, cyclophosphamide, pirarubicin, vincristine, and prednisolone) therapy and achieved complete remission for more than 1 year. Although MTX-associated lymphoproliferative disorders often show remission after withdrawal of MTX, early diagnosis and treatment are essential for PHL in patients with RA treated with MTX, because of the aggressive nature of the disease.